1996
DOI: 10.7326/0003-4819-124-9-199605010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Regimens for Treatment of Mild to Moderate Pneumocystis carinii Pneumonia in Patients with AIDS: A Double-Blind, Randomized Trial of Oral Trimethoprim-Sulfamethoxazole, Dapsone-Trimethoprim, and Clindamycin-Primaquine

Abstract: The rates of dose-limiting toxicity, therapeutic failure, and survival did not differ among patients with AIDS who were receiving oral trimethoprim-sulfamethoxazole, dapsone-trimethoprim, or clindamycin-primaquine for mild to moderate P. carinii pneumonia. However, the limited sample size prevents the unequivocal demonstration of the equality of these three regimens. Differences in expected categories of toxicities associated with each regimen should guide the clinician in choosing first-line therapy, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(99 citation statements)
references
References 24 publications
0
98
0
1
Order By: Relevance
“…Moderate to severe anemia was defined as Hb Anemia in pulmonary tuberculosis M van Lettow et al concentrations o80 g/l for both sexes according to the AIDS Clinical Trials Group classification (Safrin et al, 1996). Iron deficiency was defined as plasma ferritin concentrations o30 mg/l.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate to severe anemia was defined as Hb Anemia in pulmonary tuberculosis M van Lettow et al concentrations o80 g/l for both sexes according to the AIDS Clinical Trials Group classification (Safrin et al, 1996). Iron deficiency was defined as plasma ferritin concentrations o30 mg/l.…”
Section: Discussionmentioning
confidence: 99%
“…Liver toxicity was considered to be due to sulfadiazine alone, summative drug toxicity or a combination of drug toxicity and hepatitis B infection. Pyrimethamine-clindamycin + primaquine was the preferred regime In moderate to severe PCP, a randomised controlled comparison between intravenous co-trimoxazole 90 to 120 mg/kg/ day and pentamidine 4 mg/kg/day for 17 to 21 days demonstrated better survival rate in the co-trimoxazole arm according to Sattler et al 2 A multi-centre three-arm randomized trial in mild to moderately severe PCP reported similar two-month survival rates for trimethoprim (15 mg/ kg/day)-dapsone (100 mg/day), clindamycin 600 mg three times daily-primaquine 30 mg/day and co-trimoxazole (55-85 mg/kg/day) according to Safrin et al 3 There was no difference in proportions of patients with each therapy that had doselimiting toxicity or failure of therapy. A multi-centre, randomized comparison of atovaquone 750 mg three times daily with co-trimoxazole 1,920 mg three times daily in mild to moderately severe PCP, showed lower response rates, higher death rates attributed to PCP in the atovaquone arm, but more adverse effects requiring change of therapy in the co-trimoxazole arm, reported by Hughes et al 4 Treatment of Toxoplasma encephalitis in isolation is has also been well-studied.…”
Section: Discussionmentioning
confidence: 94%
“…22 year old African male, recently diagnosed HIV-1 positive, CD4 10 cells/mm 3 , HIV RNA 107885 copies/ml, presented to another centre, complaining of dry cough associated with night sweats for 2 weeks. He was pyrexial 39°C, sparse basal inspiratory crackles on chest examination, hypoxic with PaO 2 8.9 kPa on air and chest X-ray was unremarkable.…”
Section: Case Reportmentioning
confidence: 99%
“…El fármaco de elección para el tratamiento de la neumonía por P. jiroveci es la combinación de trimetoprim y sulfametoxazol (cotrimoxazol) 8,9 (AI) que ha sido ampliamente probado y tiene presentación iv para aquellos casos más graves que requieren manejo en una unidad de pacientes críticos (Tabla 3). Los caminos a seguir en caso de alergia al cotrimoxazol es desensibilizar 10 (Tabla 4) o recurrir a una alternativa consistente en primaquina y clindamicina 9,11,12 BI. En los casos graves con falla respiratoria (PaO 2 < 70 mmHg) es perentorio el uso de corticosteroides que pueden representar en ciertas instancias la acción terapéutica más importante para recuperar al paciente 13 .…”
Section: Tratamientounclassified